Precursor B-cell lymphoblastic lymphoma of bone in children: A close mimicker of Ewing's sarcoma - Shwetha Seetharam; Priyakumari Thankamony; Priya Mary Jacob; Rekha Appukuttan Nair (Indian Journal of Medical and Paediatric Oncology)
Precursor B-cell lymphoblastic lymphoma (LBL) occurring as a primary bone tumor is a rare clinical presentation in children, and data regarding this condition are limited to small case series or a few individual case reports. We report two pediatric cases of precursor B-cell LBL of the bone. The tumor cells from bone biopsies of both patients were seen to be positive for leukocyte common antigen (LCA), terminal deoxynucleotidyl transferase, CD10, CD20 and weakly positive for CD99. Bone marrow studies were normal. They were treated according to the modified Berlin-Frankfurt-Münster acute lymphoblastic leukemia high-risk protocol. The first patient has completed treatment including local radiotherapy and has been disease free for the past 10 years. The second patient has recently completed treatment and shows good response.